Clean coal use in China: Challenges and policy implications. (December 2015) - Tang, Xu; Snowden, Simon; McLellan, Benjamin C.; Höök, Mikael
Abstract: Energy consumption in China is currently dominated by coal, a major source of air pollution and carbon emissions. The utilization of clean coal technologies is a likely strategic choice for China at present, however, although there have been many successes in clean coal technologies worldwide, they are not widely used in China. This paper examines the challenges that China faces in the implementation of such clean coal technologies, where the analysis shows that those drivers that have a negative bearing on the utilization of clean coal in China are mainly non-technical factors such as the low legal liability of atmospheric pollution related to coal use, and the lack of laws and mandatory regulations for clean coal use in China. Policies for the development of clean coal technologies are in their early stages in China, and the lack of laws and detailed implementation requirements for clean coal require resolution in order to accelerate China's clean coal developments. Currently, environmental pollution has gained widespread attention from the wider Chinese populace and taking advantage of this opportunity provides a space in which to regain the initiative to raise people's awareness of clean coal products, and improve enterprises' enthusiasm for clean coal. Highlights: Clean coal is not widely used in China due to many management issues. Legal liability of pollution related with coal utilization is too low in China. China is lack of laws and mandatory regulations for clean coal utilization. It is difficult to accelerate clean coal utilization by incentive subsidies alone.